(untitled) (Eastern Journal of Medical Sciences, 2017)
Tuberculosis (TB) is one of the oldest diseases known to affect human being. In 2012, out of the estimated global annual incidenceof 8.6 million TB cases, 2.3 million were estimated to have occurred in India. The disease is responsible for killing more women ofreproductive age than all the combined causes of maternal mortality. The exact incidence of TB in pregnancy is not readily availablein many countries due to a lot of confounding factors. It is, however, expected that the incidence of TB among pregnant womenwould be as high as in the general population, with possibly higher incidence in developing countries. Pregnancy has no positiveor negative impact on TB. The clinical presentation of TB is similar to nonpregnant woman but the diagnosis is often delayeddue to nonspecific early symptoms and has similar constitutional symptoms like malaise and fatigueness found in pregnancy. Thebacteriological diagnosis sample should be processed for tests such as ZN-stain, light-emitting diode microscopy, Gene-Xpert,and gold standard test culture. Treatment of non-multi-drug resistance (MDR) patients should be treated by the same regimen asnonpregnant patients except the use of Streptomycin. The most of the second-line anti-TB drugs are teratogenic and so expectedmother with MDR-TB should be advised to terminate the pregnancy.